Brong Exhaust Policy Implementation by the Purbalingga Police: A Public Administration Perspective - Syafruddin Syafruddin; David Raditya Yudhistira; Bayu Suseno; Rina Yulianti; Juliannes Cadith (Glosains: Jurnal Sains Global Indonesia, 2026)
Background: Brong exhaust modification has not only been widespread in Purbalingga but has also caused noise pollution and public inconvenience, as well as constituting a criminal offense. In response, the Purbalingga Police released a brong exhaust handling policy referring to Police Chief Regulation Number 5 of 2022. Objective: This research aimed to assess the effect of policy implementation from the perspective of public administration. Methods: The research method used was qualitative descriptive, involving seven informants from the Purbalingga Police Traffic Unit and affected motorists, with data collected through in-depth interviews with police officers from the Purbalingga Police Traffic Unit and motorists affected by raids, field observations, and document studies. The data were analyzed using the Miles and Huberman interactive model. Results: Results show that the policy is largely suboptimal in its current form. Challenges such as a lack of human resources and the absence of noise-measuring instruments were identified. Coordination between related agencies such as Dishub was also suboptimal, and public awareness of legal obligations remains low. From a public administration perspective, the key factors identified are communication, resources, and implementer disposition. Conclusion: The implementation of the brong exhaust policy by the Purbalingga Police has not been fully optimal due to limited personnel, the absence of noise-measuring instruments, and suboptimal cross-sector coordination. Officer discretion plays a significant role in shaping enforcement outcomes. Policy reform should prioritize technical capacity building, structured inter-agency collaboration, and contextual enforcement strategies that balance law enforcement with the protection of Purbalingga's brong exhaust industry as a key local livelihood.